Matarrah: A Southern Variant of the Hassunan Assemblage, Excavated in 1948 - Braidwood, R. J.
Introduction — The Matarrah Assemblage (1. Introduction — 2. Architecture — 3. Pottery — 4. Pottery Objects — 5. Flaked-Stone Industry — 6. Ground-Stone Industry — 7. Bone Industry — 8. Other Materials — 9. Burials — 10. Nonartifactual Materials) — Style Tradition and Change: An Analysis of the Earliest Painted Pottery from North Iraq — Conclusions - Appendixes.